Classical physics experiments in the amusement park - Bagge, Sara; Pendrill, Ann Marie ; 0000-0002-1405-6561 (Physics Education, 2002)
An amusement park is a large physics laboratory, full of rotating and accelerated coordinate systems. The forces are experienced throughout the body and can be studied with simple equipment or with electronics depending on age and experience. In this paper, we propose adaptations of classical physics experiments for use on traditional rides.